Analysis of the expression and distribution of protein O-linked mannose β1,2-N-acetylglucosaminyltransferase 1 in the normal adult mouse brain - Jiang, Hanxiao; Feng, Yuxue; He, Guiqiong; Liu, Yuanjie; Li, Xiaofeng (Frontiers in Neuroanatomy, 2023)
Introduction Protein O-linked mannose β1,2-N-acetylglucosaminyltransferase 1 (POMGNT1) is crucial for the elongation of O-mannosyl glycans. Mutations in POMGNT1 cause muscle-eye-brain (MEB) disease, one of the main features of which is anatomical aberrations in the brain. A growing number of studies have shown that defects in POMGNT1 affect neuronal migration and distribution, disrupt basement membranes, and misalign Cajal-Retzius cells. Several studies have examined the distribution and expression of POMGNT1 in the fetal or neonatal brain for neurodevelopmental studies in the mouse or human brain. However, little is known about the neuroanatomical distribution and expression of POMGNT1 in the normal adult mouse brain. Methods We analyzed the expression of POMGNT1 mRNA and protein in the brains of various neuroanatomical regions and spinal cords by western blotting and RT-qPCR. We also detected the distribution profile of POMGnT1 in normal adult mouse brains by immunohistochemistry and double-immunofluorescence. Results In the present study, we found that POMGNT1-positive cells were widely distributed in various regions of the brain, with high levels of expression in the cerebral cortex and hippocampus. In terms of cell type, POMGNT1 was predominantly expressed in neurons and was mainly enriched in glutamatergic neurons; to a lesser extent, it was expressed in glial cells. At the subcellular level, POMGNT1 was mainly co-localized with the Golgi apparatus, but expression in the endoplasmic reticulum and mitochondria could not be excluded. Discussion The present study suggests that POMGNT1, although widely expressed in various brain regions, may has some regional and cellular specificity, and the outcomes of this study provide a new laboratory basis for revealing the possible involvement of POMGNT1 in normal physiological functions of the brain from a morphological perspective.